Avaliação da expressão das moléculas CD80, CD86 e MHCII em eosinófilos durante a síndrome da larva migrans visceral - Rodolpho, Joice Margareth de Almeida (2012)
Eosinophils are a hematopoietic cell originated from precursor cells found in bone marrow, whose differentiation and proliferation is regulated by cytokines such as GM-CSF, IL-3 and IL-5. When activated, eosinophils are capable of phagocytosis of small particles and bacteria, but their main form of activity in the inflammatory process is the release of toxic proteins, cytokines, enzymes, lipid mediators and reactive oxygen products. The increase in eosinophil is an important feature in many diseases such as allergy and parasitic infections. Provided APC (Antigen-Presenting Cells), eosinophils are considered similar to the CD (Dendritic Cells) in its potential to activate naïve T cells and may have potential as efficient as the CD in stimulating lung T cells in the upper airways in the model inflammation. The APC are defined by being able to take, processing and presenting antigen such as CD, macrophages, B lymphocytes and possibly eosinophils. The surface expression of APC is characterized by coestimatórias molecules CD80 (B7-1) and CD86 (B7-2) and also by MHCII. The proposed model for this evaluation was to Visceral Larva Migrans syndrome (VLMS) caused by Toxocara canis, one of the most frequent helminth in young dogs. One of the main consequences of this infection is the marked increase in circulating and tissue eosinophils. Eosinophilia has been associated with parasitic diseases particularly when the parasite invades or promotes tissue damage at mucosal surfaces In the present study we evaluated the expression of MHC II and CD80 and CD86 molecules coestimulatórias in eosinophils in VLMS. Our results showed that the molecules studied were expressed in eosinophils in the blood of mice infected with Toxocara canis compared with the control group. Correlating an intense eosinophil still during the course of the disease with increased IL-5 in the infected group. Suggests that during the course of Toxocara canis, eosinophils can exhibit behavior of an APC, increasing the expression of MHCII molecules coestimulatorias and possibily amplifyng the immune response in this model.